Traditional knowledge regarding entomophagy in San Martín, Peruvian Amazon - Cerna, A. (2021)
The consumption of insects is a widespread practice among indigenous or native peoples of the Amazon. To assess the knowledge of the diversity of resources for entomophagy from the perspective of these peoples, testimonies or references about knowledge and feeding traditions of 100 people were collected in 37 localities in seven provinces of the department of San Martín in the basin of the Huallaga River. One cumulative species curve and the probability function of new species were estimated, then the probability of not finding a new species (99.5 %) to n100 was determined. The specimens that were captured in the field (54 %) were compared with representative specimens and databases, and the information provided by the participants was analysed to approximate the preliminary taxonomic locations of the remaining part of the sample. We found 46 resources for entomophagy and reported for first time in the Peruvian Amazon, the feeding with Chrysophora chrysochlora, Podalia sp., Lusura chera, and Cymothoidae, among others. Entomophagy is a deeply rooted practice in the native and riverine populations of the Huallaga basin, where Rhynchophorus palmarum, Rhinostomus barbirostris, Atta cephalotes sspp. and Brassolis sophorae were the most consumed for 78 % – 97 % of people. The least consumed species have the common characteristic of being scarce and they were part of the diet of the oldest segment in previous decades. At least 10 resources ceased to be consumed by the members of the sample. In addition to nutritional potential, the diversity of edible arthropod fauna represents complementary values for community health and cultural identity; however, most of these resources (87 %) are threatened and could disappear in brief time, as is the knowledge related to their use.